Baranova S. V. “Philosophy” of quantitative-qualitative relations - Baranova S. V. (Philological Treatises, 2020)
The article deals with the problem of language and thinking connection, categories of quantity and quality are considered. Quantitativeness and qualitativeness are investigated, logical and philosophical bases of the corresponding language categories are defined.